Health literacy and associated factors among undergraduates: A university-based cross-sectional study in Nepal - Sandesh Bhusal; Rajan Paudel; Milan Gaihre; Kiran Paudel; Tara Ballav Adhikari; Pranil Man Singh Pradhan (Public Library of Science (PLoS), 2021)
Health literacy is one of the most critical aspects of health promotion. Limited health literacy is also accounted for adverse health outcomes and a huge financial burden on society. However, a gap exists in the level of health literacy, especially among undergraduates. This study aimed to assess the levels of health literacy and its socio-demographic determinants among undergraduate students of Tribhuvan University, Nepal. A web-based cross-sectional survey was conducted among 469 undergraduate students from five institutes of Tribhuvan University, Nepal. The 16-item short version of the European Health Literacy Survey Questionnaire (HLS-EU-Q16) was used to measure students' health literacy levels. Associated factors were examined using Chi-square tests followed by multivariate logistic regression analyses at the level of significance of 0.05. Nearly 61% of students were found to have limited health literacy (24.5% had "inadequate" and 36.3% had "problematic" health literacy). Female students (aOR = 1.6, 95% CI: 1.1-2.5), students from non-health related majors (aOR = 1.9, 95% CI: 1.2-3.0), students with unsatisfactory health status (aOR = 2.8, 95% CI: 1.7-4.5), students with poor financial status (aOR = 2.9, 95% CI: 1.2-6.8) and students with low self-esteem (aOR = 2.5, 95% CI: 1.5-4.1) were significantly more likely to have limited health literacy. The majority of the undergraduates were found to have limited health literacy. Gender, sector of study, self-rated health status, self-rated financial status, and self-esteem were significantly associated with limited health literacy. This study indicates university students should not be assumed to be health-literate and interventions to improve students' health literacy especially for those whose majors are not health-related should be implemented. Further studies using a longer version of the health literacy survey questionnaire and qualitative methods to explore more on determinants of health literacy are recommended.